Apply High Order Thinking Skills in Science Lessons in Primary School - Jeanne Mangangantung; Roos M.S Tuerah (International Journal of Education, Information Technology, and Others, 2021)
The ability of teachers to make questions and in compiling a Learning Implementation Plan (RPP) that contains elements of high-level thinking skills is something that absolutely must have. Through training activities on Higher Level Thinking Skills (HOTS), it is expected that science teachers in elementary schools are able to implement these thinking skills to students in their respective schools. For teachers here is a field to explore their abilities by trying to train high-level thinking skills in elementary school students. With sufficient levels of difficulty and dynamic learning activities, students must be able to develop their minds to understand the material being studied, not enough just to follow the instructions in the book, but they also need to be able to develop each stage of learning by processing existing data and information to be developed in more ways of thinking, so that they can find various other concepts, as innovative steps.